2012
DOI: 10.1371/journal.pcbi.1002708
|View full text |Cite
|
Sign up to set email alerts
|

CAVER 3.0: A Tool for the Analysis of Transport Pathways in Dynamic Protein Structures

Abstract: Tunnels and channels facilitate the transport of small molecules, ions and water solvent in a large variety of proteins. Characteristics of individual transport pathways, including their geometry, physico-chemical properties and dynamics are instrumental for understanding of structure-function relationships of these proteins, for the design of new inhibitors and construction of improved biocatalysts. CAVER is a software tool widely used for the identification and characterization of transport pathways in stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
1,081
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,070 publications
(1,137 citation statements)
references
References 61 publications
9
1,081
1
4
Order By: Relevance
“…Most of the outliers are located in the integral membrane subunits or areas where the electron density was less well defined. Cavities and putative channels were calculated with CAVER 51 , and surface potential was calculated with APBS 52 . All figures were pre pared with PyMol 53 .…”
Section: Methodsmentioning
confidence: 99%
“…Most of the outliers are located in the integral membrane subunits or areas where the electron density was less well defined. Cavities and putative channels were calculated with CAVER 51 , and surface potential was calculated with APBS 52 . All figures were pre pared with PyMol 53 .…”
Section: Methodsmentioning
confidence: 99%
“…4A). Interestingly, the visual and automatic analyses of the CIPK23ΔC T190D and CIPK24/SOS2ΔC T168D molecular surfaces using CAVER (48) reveal that the ATP cavity spans linearly, wrapping the kinase domain around the hinge region between the N and C lobes (Fig. 4A).…”
Section: Cipk23 and Cipk24/sos2 Adopt A Conserved Inactive Conformationmentioning
confidence: 99%
“…Importantly, the disposition of pores in the Bot1 model and in the uracil/H + symporter structure, the latter used as an initial template for simulations, showed similar spatial characteristics. Evaluations of predicted pore dimensions of Bot1 (Chovancova et al, 2012) revealed that in the wild-type and mutagenized variants with preserved transport function, the pores penetrated through the a-helical bundle, while only short tunnels were formed in non-transporting variants (Supplemental Tables 2 and 3 and Supplemental Figure 8). …”
Section: Bot1 Protrudes 17 Nm Above the Bilayer Surfacementioning
confidence: 99%
“…The dimensions of pores in wild-type and variants of Bot1 were calculated by Caver3.0 (Chovancova et al, 2012) using an ensemble of 50 snapshots deduced from each trajectory. Identified pores resulted from a series of associated spheres and sphere radii and corresponded to the closest distances to protein atoms.…”
Section: Pore Dimension Calculationsmentioning
confidence: 99%